Professor Jerzy Sadowski 1924–2014 - SZUDROWICZ, Barbara (Archives of Acoustics, 2014)
Professor Jerzy Sadowski – outstanding Polish scientist, a specialist in acoustics – construction, industrial, architectural and environmental – passed away on 28th July 2014.Professor Jerzy Sadowski was born on 18th December 1924 in Augustów, in northeastern Poland. In 1946 he commenced studies at the Gdańsk University of Technology – initially at the Faculty of Architecture, to switch later to the Faculty of Electrical Engineering. The life of Jerzy Sadowski as a student was as complicated as the post-war history of Poland. Due to his involvement in an activity of illegal student organization, he was expelled from the university in 1949, with a ban on any further tertiary education. The ban had been lifted after a certain time which allowed him to recommence further studies, this time at the Warsaw University of Technology the Faculty of Communications, where in 1952 he obtained the diploma and title of Master of Science and Engineer. He received a lot of help from Professor Ignacy Malecki, the nestor of Polish acoustics. This certainly contributed to kindling the young engineer’s interest in acoustics, as a field of both knowledge and very important practical applications.